Mathematical analysis of placental weight ratio: Newborn in height - Sobrevilla, Luis (2015)
We have taken as data for the statistical study of 26 consecutive observations weight of newborn and placenta in Lima (150 m.) And 29 in Cerro de Pasco (4,200 m.). Sibien studying the technical data of the randomized comparison of two groups showed no significant difference between placental weights, covariance analysis indicates that increasing the height influence placental weight significantly (F <0.001), in while the weight of the newborn becomes smaller.